LGBTQ intimate partner violence: lessons for policy, practice, and research - Messinger, Adam M. (University of California Press, 2017)
"Nationally representative studies confirm that LGBTQ individuals are at an elevated risk of experiencing intimate partner violence. While many similarities exist between LGBTQ and heterosexual intimate partner violence, research has illuminated a variety of unique aspects of LGBTQ intimate partner violence regarding the predictors of perpetration, the specific forms of abuse experienced, barriers to help-seeking for victims, and policy and intervention needs. This is the first book that systematically reviews the literature regarding LGBTQ intimate partner violence, draws key lessons for current practice and policy, and recommends research areas and enhanced methodologies."--Provided by publisher